2021
DOI: 10.1177/2040622321991705
|View full text |Cite
|
Sign up to set email alerts
|

Serum-derived exosomes containing NEAT1 promote the occurrence of rheumatoid arthritis through regulation of miR-144-3p/ROCK2 axis

Abstract: Background: Evidence has demonstrated that non-coding RNAs (ncRNAs) could be delivered efficiently to recipient cells using exosomes as a carrier. Additionally, long ncRNA nuclear enriched abundant transcript 1 (NEAT1) is emerging as a vital regulatory molecule in the progression of rheumatoid arthritis (RA). The aim of this study was to identify the NEAT1/miR-144-3p/Rho-associated protein kinase 2 (ROCK2) functional network regulating the WNT signaling pathway in RA. Methods: In vivo, a collagen-induced arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The possible reasons might be that: (a) elevated lnc‐NEAT1 and decreased miR‐21 and miR‐125a could promote inflammatory cytokines and immune response, which consequently resulted in elevated inflammation in RA patients 7 , 19 , 20 , 23 ; and (b) increased lnc‐NEAT1 and declined miR‐21 and miR‐125a might inhibit new bone formation and accelerate bone degradation through regulating several signaling pathways (such as Janus kinase 2/signal transducer, activator of transcription‐3, and E26 transformation‐specific‐1 pathways), which could lead to high disease activity in RA patients. 24 , 25 , 26 Therefore, elevated lnc‐NEAT1 but declined miR‐21 and miR‐125a were correlated with inflammation and disease activity in RA.…”
Section: Discussionmentioning
confidence: 94%
“…The possible reasons might be that: (a) elevated lnc‐NEAT1 and decreased miR‐21 and miR‐125a could promote inflammatory cytokines and immune response, which consequently resulted in elevated inflammation in RA patients 7 , 19 , 20 , 23 ; and (b) increased lnc‐NEAT1 and declined miR‐21 and miR‐125a might inhibit new bone formation and accelerate bone degradation through regulating several signaling pathways (such as Janus kinase 2/signal transducer, activator of transcription‐3, and E26 transformation‐specific‐1 pathways), which could lead to high disease activity in RA patients. 24 , 25 , 26 Therefore, elevated lnc‐NEAT1 but declined miR‐21 and miR‐125a were correlated with inflammation and disease activity in RA.…”
Section: Discussionmentioning
confidence: 94%
“…That study provides new ideas for the osteogenic effects of exosomes in BMSCs carrying specific tsRNAs on SONFH. Besides, there is evidence that exosomal lncRNA nuclear enriched abundant transcript (NEAT)1 isolated from the serum of patients with rheumatoid arthritis can promote the development of rheumatoid arthritis through the miR-144-3p/ROCK2 axis ( Liu et al, 2021 ). This NEAT1/ miR-144–3p/ROCK2 regulatory pathway may become a new treatment target for rheumatoid arthritis.…”
Section: Clinical Potential Of Exosomal Ncrnas In Bone-related Diseasesmentioning
confidence: 99%
“…Subsequent studies have also shown that, compared with the exosomes from normal controls (n=20), there was a significant increase in the expression of NEAT1 in the exosomes of patients with RA (n=68). Also, NEAT1 might act as a ceRNA for miR144-3p to restrict its function, and thus increase the expression of the miR144-3p-targeted gene (Rho associated coiled-coil containing protein kinase 2, ROCK2) in CD4 + T cells, promoting the progression of RA ( 129 ). Another study showed that the levels of a set of lncRNAs, HOTAIR, Luca-15 Specific Transcript (LUST), anti-NOS2A, MEG, TUG1, NEAT1, Small Nucleolar RNA Host Gene 4 (SNHG4), Highly Accelerated Region 1B (HAR1B), and GAS5, have higher expression levels in seral exosomes of patients with RA (n=28) than in the seral exosomes of normal controls (n=10) ( 89 ).…”
Section: Lncrna and Ramentioning
confidence: 99%